Multiple missions in the midst of war - Bergmann, Julian,Kosmehl, Miriam,Langbein, Julia,Sasse, Gwendolyn (German Institute of Development and Sustainability (IDOS) gGmbH, 2024)
Ukraine and its international partners are faced with an unprecedented task: advancing recovery efforts and the EU accession process while also providing critically important military and financial support to help Ukraine defend its sovereignty against Russian military aggression. Uncertainty over when and how the war will end makes planning for recovery and EU membership even more complex, but also underlines the need for their integration. Given a shared focus on a transformative modernisation, both processes can reinforce each other. Along this line of thinking, the EU has adopted the Ukraine Facility to provide reliable funding to Ukraine up to 2027, with the aim of supporting recovery and key institutional and administrative reforms required for Ukraine's EU accession. The main roadmap for implementation of both is the Ukrainian government's so-called Ukraine Plan. However, recovery and EU accession will not automatically create synergies, and may, at worst, overstretch Ukrainian government and private-sector capacities as well as societal support. To maximise synergies between the processes, policymakers should consider the following recommendations: ● Set priorities that address short-term demands and have long-term ambitions. Recovery measures should be prioritised that improve security, meet the basic needs of the people and are crucial to the functioning of the Ukrainian economy. In EU accession negotiations, the
10419/294866
Keywords: Graue Literatur; Wiederaufbau; Kriegsfolge; Internationale Organisation; Erweiterung; Verhandlung; Beitritt; Kapitalhilfe; Zivilgesellschaft; Information; Kommunikation; Wirkung; Auswirkung; Krieg; Ukraine; Ukraine-EU relations; recovery; reconstruction; EU accession; EU enlargement policy